1999
DOI: 10.1159/000012069
|View full text |Cite
|
Sign up to set email alerts
|

p53 Autoantibodies in Patients with Primary Ovarian Cancer Are Associated with Higher Age, Advanced Stage and a Higher Proportion of p53-Positive Tumor Cells

Abstract: Autoantibodies (AAb) directed against the nuclear phosphoprotein p53 can be detected in patients with various forms of cancer. The objective was to determine the prevalence of p53 AAb at the time of diagnosis in ovarian cancer patients and to correlate the presence of p53 AAb with clinicopathological parameters. Sera of 83 patients were analyzed by an ELISA using p53 expressed from a human wild-type cDNA. p53 AAb were detectable at all stages. The overall prevalence was 46%. p53 AAb were more frequent in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…Reports from Vogl and colleagues [23] revealed 46% prevalence of circulating p53 autoantibodies in a study population comprising 83 OVCA patients. Their study also indicated that in a bivariate analysis, patients with anti-p53 autoantibodies had a 1.96-fold risk for relapse (95% confidence interval 1.02–3.78).…”
Section: Discussionmentioning
confidence: 99%
“…Reports from Vogl and colleagues [23] revealed 46% prevalence of circulating p53 autoantibodies in a study population comprising 83 OVCA patients. Their study also indicated that in a bivariate analysis, patients with anti-p53 autoantibodies had a 1.96-fold risk for relapse (95% confidence interval 1.02–3.78).…”
Section: Discussionmentioning
confidence: 99%
“…30 OVCA cells express mutated forms of p53 [31][32][33] and/or BRCA-1 34,35 tumor suppressor genes. Ovarian tumor cells also express high levels of the CA-125 [36][37][38] and MUC1 39 TAA.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA assisted by the recombinant p53 protein is a simple and reliable method to detect p53 Abs in serum (12). The frequency of serum p53 Abs in ovarian cancer is still controversial in previous reports (13)(14)(15)(16). So it's necessary to analyze p53 Abs in serum from patients with ovarian cancer systematically.…”
Section: Discussionmentioning
confidence: 99%